The Direction Of Future Management Accounting Research In The Asia Pacific Region - Grahita Chandrarin (UBL, 2013)
The direction of development of management accounting research is line with the shift of paradigm ofmanagement accounting in practice supported by development of information technology. The directionwill lead to the new strategy that moves to contemporary management accounting.Today, competition among companies in many industries is turning global. To be competitive,businesses must adopt new ways of thinking about business to improve the old management practices.Since 1990s, contemporary management accounting concept has moved from traditional managementaccounting concept with focuses on technical issues, so that become behavior centered. This is to say thatglobal competition requires companies to use bottom-up information that empowers the work force tocontrol processes for customer satisfaction. To stimulate competitiveness, management information mustfollow the bottom-up empowerment cycle. It must come from customers and processes that must begathered and used primarily by people in the work force who face customers and run the processes.This paper explains how the paradigm shifts from conventional accounting management tocontemporary accounting management in practice and research. Therefore, It recommend that thedirection of management accounting research in Asia Pacific region on the future should cover all studiesincluded in contemporary accounting management area, that holds the idea that contemporarymanagement practice does not only focus on profit but also social and environmental factors forsustainability